2020
DOI: 10.3390/ijms21239023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Use of a PBMC-Based Functional Assay to Identify Predictive Biomarkers for Anti-PD-1 Immunotherapy

Abstract: The absence of reliable, robust, and non-invasive biomarkers for anti- Programmed cell death protein 1 (PD-1) immunotherapy is an urgent unmet medical need for the treatment of cancer patients. No predictive biomarkers have been established based on the direct assessment of T cell functions, the primary mechanism of action of anti-PD-1 therapy. In this study, we established a model system to test T cell functions modulated by Nivolumab using anti-CD3 monoclonal antibody (mAb)-stimulated peripheral blood mononu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Our data show that the levels of IL-10 induced by nivolumab or pembrolizumab are highly heterogeneous. Consistent with this, our recent studies also showed that nivolumab induces IL-10 production using a PBMC-based assay [ 45 ]. This is consistent with a recent report that elevated IL-10 levels caused by anti-PD-1 mAb treatment were also found in an animal tumor model [ 25 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data show that the levels of IL-10 induced by nivolumab or pembrolizumab are highly heterogeneous. Consistent with this, our recent studies also showed that nivolumab induces IL-10 production using a PBMC-based assay [ 45 ]. This is consistent with a recent report that elevated IL-10 levels caused by anti-PD-1 mAb treatment were also found in an animal tumor model [ 25 ].…”
Section: Discussionsupporting
confidence: 78%
“…The mechanisms underlying these challenges are not fully understood [ 6 , 8 , 41 , 42 , 43 , 44 ]. IL-10 is one of the most important immunoregulatory cytokines that regulates the T cell response via modulating multiple signaling pathways [ 12 , 14 , 15 , 25 , 45 ]. In the present study, we describe that nivolumab induces potent IL-10 secretion in T cells due to activation of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ICT with anti-PD-1 and anti-PD-L1 therapy has completely changed the treatment of various advanced cancers ( Bacot et al, 2020 ), including EC. Despite immune checkpoint inhibitors (ICI) can significantly improve the prognosis of patients with EC, there are still a considerable proportion of patients who have no response or resistance to ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, foreign body reaction is mediated by Th17 cells, 6 whose reaction can be enhanced by immune checkpoint inhibitor. 7 Several cases showed an immune reaction to nonabsorbent surgical sutures, leading to abscess formation 8 ; therefore, the enhancement of immune reaction by immune checkpoint inhibitors might develop a foreign body reaction to a nonabsorbent surgical suture. The second reason was a reaction to the scar after the appendectomy.…”
Section: A Subcutaneous Abscess Following Anti-programmed Cell Death ...mentioning
confidence: 99%